Mixing alternating copolymers containing fluorenyl groups with phospholipids to obtain Langmuir and Langmuir-Blodgett films - Santos, Thays C F (Langmuir : the ACS journal of surfaces and colloids, 2010)
The control of molecular architectures may be essential to optimize materials properties for producing luminescent devices from polymers, especially in the blue region of the spectrum. In this Article, we report on the fabrication of Langmuir-Blodgett (LB) films of polyfluorene copolymers mixed with the phospholipid dimyristoyl phosphatidic acid (DMPA). The copolymers poly(9,9-dioctylfluorene)-co-phenylene (copolymer 1) and poly(9,9-dioctylfluorene)-co-quaterphenylene) (copolymer 2) were synthesized via Suzuki reaction. Copolymer 1 could not form a monolayer on its own, but it yielded stable films when mixed with DMPA. In contrast, Langmuir monolayers could be formed from either the neat copolymer 2 or when mixed with DMPA. The surface pressure and surface potential measurements, in addition to Brewster angle microscopy, indicated that DMPA provided a suitable matrix for copolymer 1 to form a stable Langmuir film, amenable to transfer as LB films, while enhancing the ability of copolymer 2 to form LB films with enhanced emission, as indicated by fluorescence spectroscopy. Because a high emission was obtained with the mixed LB films and since the molecular-level interactions between the film components can be tuned by changing the experimental conditions to allow for further optimization, one may envisage applications of these films in optical devices such as organic light-emitting diodes (OLEDs)